Assessment on the ownership and use of mosquito nets in Mozambique - Jorge Alexandre Harrison Arroz; Francisco Chirrute; Chandana Mendis; Marta Honesta Chande; Veronique Kollhoff (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To assess the ownership and use of mosquito nets in 2014, in Mozambique. METHODS This observational and cross-sectional study assessed, in February and March 2015, 69 districts (nine of 11 provinces of Mozambique) that have benefited from the mass distribution of mosquito nets. The Lot Quality Assurance Sampling methodology was used. Each locality was denominated supervision area. The Lot Quality Assurance Sampling opts for a minimum of 19 households (in this case, we decided for a minimum of 100 households per district) from each supervision area to assess an indicator (in this case, two indicators were assessed: ownership and use of mosquito nets). Two questions guided the research: a) received a mosquito net; b) used a mosquito net the night before. RESULTS A total of 6,725 households were assessed. Eighty three percent of them had received mosquito nets in the campaign. Of the 6,232 respondents, 82.0% said they used mosquito nets the night before. The districts of the provinces with low coverage of ownership and use were Tete (69.5% and 60.0%, respectively), Zambezia (79.0% and 60.0%, respectively), and Gaza (81.6% and 70.7%, respectively). The largest coverage of ownership and use were observed in the districts of Nampula (96.7% and 93.8%, respectively) and Niassa (86.0% and 85.4% respectively). CONCLUSIONS In the districts assessed, the progression of ownership and use of mosquito nets is satisfactory. Nampula and Niassa are the only provinces where ownership and use are at desired levels.